Santri Husada Cadres Empowerment as Promotive and Preventive Agents at Pondok Pesantren Jabal Noer - Atik Qurrota A'Yunin Al Isyrofi; Wiwik Afridah; Merry Soenaryo; Marselli Widya Lestari; Fahrizal Amin Nurfaizi (Universitas Nahdlatul Ulama Surabaya, 2023)
Pondok Pesantren (PP) Jabal Noer faces a double burden of health problems, both communicable and non-communicable diseases. These problems arise due to various factors, especially behavioral and environmental factors. Furthermore, there were also health service problems which makes suboptimal prevention efforts. Pos Kesehatan Pesantren (Poskestren) has not yet functioned as a center for promotive and preventive services. Therefore, the aim of this article is to explain alternative empowerment method that can be carried out to optimize the role of Poskestren cadres as promotive and preventive agents. This community empowerment involves the entire Pesantren community with santri husada cadres who are the key population as agents of change. Cadre empowerment was carried out through training activities and coaching of santri husada cadres every week for around 2 (two) months. After that, cadres are also provided with assistance in developing promotive and preventive programs as well as monitoring and evaluation so that the empowerment process can be sustainable. The results of the community empowerment were 75% of santri husada cadres have experienced an increase in their knowledge and promotive and preventive skills. In addition, 70% of programs developed by cadres through Poskestren have been designed to focus on their main roles and functions in promotive and preventive aspects. Empowering Pesantren community absolutely needs to involve the participation of santri as a key population which in this case can be mobilized by santri husada cadres as promotive and preventive agents. There needs to be a reorientation of health services in Pesantren, so that Pesantren community is not just an object, but must be positioned as subjects who are actively involved in health services.